An Australian land mammal age biochronological scheme. Issue 4 (8th April 2010) - Megirian, Dirk; Prideaux, Gavin J.; Murray, Peter F.; Smit, Neil
Abstract : Constrained seriation of a species-locality matrix of the Australian Cenozoic mammal record resolves a preliminary sixfold succession of land mammal ages apparently spanning the late Oligocene to the present. The applied conditions of local chronostratigraphic succession and inferences of relative stage-of-evolution biochronology lead to the expression of a continental geological timescale consisting of, from the base, the Etadunnan, Wipajirian, Camfieldian, Waitean, Tirarian, and Naracoortean land mammal ages. Approximately 99% of the 360 fossil assemblages analyzed are classifiable using this method. Each is characterized by a diagnostic suite of species. An interval of age magnitude may eventually be shown to lie between the Camfieldian and Waitean, but is currently insufficiently represented by fossils to diagnose. Development of a land mammal age framework marks a progressive step in Australian vertebrate biochronology, previously expressed only in terms of local faunas. Overall, however, the record remains poorly calibrated to the Standard Chronostratigraphic Scale. Codifying the empirical record as a land mammal age sequence provides an objective basis for expressing faunal succession without resort to standard chronostratigraphic terms with the attendant (and hitherto commonly taken) risks of miscorrelating poorly dated Australian events to well-dated global events.